Electro- and magneto-rheological materials - de Abreu, Gustavo Luiz Chagas Manhaes [UNESP]; Marques, Flavio Donizeti; de Almeida, Fabricio Cesar Lobato [UNESP]; Paschoalini, Amarildo Tabone [UNESP]; Bellucci, Felipe Silva (Springer Nature, 2016)
Novel materials suitable for engineering applications are under development in a number of research centers. Among them, fluids and gels that can change their rheological properties start to grow in importance for smart structures applications. Such materials usually present changes in their properties due to action of an external field, such as electric or magnetic. It has been observed that changes may occur very fast, allowing applications in active control, for instance. There are two main classes of the so-called smart fluids, one exploiting the electro-rheological (ER) effect, and the other exploiting the magnetorheological (MR) effect. These variable rheology fluids can have their mechanical properties modeled in terms of different behaviors of the field-dependent stress- strain curve. For the pre-yield region of the stress-strain curve the fluid behaves like a viscoelastic material, then as plastic in the post-yield region, and as viscoelastic- plastic in the transition through yield region. Considering that smart fluids exhibit linear shear behavior at small strain levels, similar to many viscoelastic materials, it is convenient to model variable rheology fluids with the same approaches developed for viscoelastically damped structures. As a study case, a sandwich beam with ER fluid core is modeled with finite element method. The dynamical behavior is assessed with the Golla-Hughes-McTavish (GHM) method to incorporate the frequency dependence properties of the ER fluid in a structural time domain model, admitting its behavior as viscoelastic and dependent on an electric field. The results are compared with analytical models and experimental data available in literature, aiming to illustrate the potential of variable rheology fluids in further smart structures concepts.
Keywords: ER/MR fluids; GHM method; Intelligent materials; Viscoelastic materials